2013
DOI: 10.7314/apjcp.2013.14.10.5783
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek Induced Apoptosis in Breast Cancer MCF-7 Cells Mediated Independently by Fas Receptor Change

Abstract: Trigonella foenum in graecum (Fenugreek) is a traditional herbal plant used to treat disorders like diabetes, high cholesterol, wounds, inflammation, gastrointestinal ailments, and it is believed to have anti-tumor properties, although the mechanisms for the activity remain to be elucidated. In this study, we prepared a methanol extract from Fenugreek whole plants and investigated the mechanism involved in its growth-inhibitory effect on MCF-7 human breast cancer cells. Apoptosis of MCF-7 cells was evidenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In due course our group already has demonstrated the anti-preoperative potential of organic extracts from root bark of Juglans Regia against MDA-MB-231 human breast cancer cells (Hasan et al, 2011). In addition of that, our group also demonstrated that methanolic extract of fenugreek whole plant (without root) has potential to induce apoptosis in MCF-7 human breast cancer cells through the involvement of Fas receptor and Caspase-8 (Alshatwi et al, 2013). In present study we are focusing on the anti cancer and apotosis inducing ability of NS seed extract in MCF-7 human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In due course our group already has demonstrated the anti-preoperative potential of organic extracts from root bark of Juglans Regia against MDA-MB-231 human breast cancer cells (Hasan et al, 2011). In addition of that, our group also demonstrated that methanolic extract of fenugreek whole plant (without root) has potential to induce apoptosis in MCF-7 human breast cancer cells through the involvement of Fas receptor and Caspase-8 (Alshatwi et al, 2013). In present study we are focusing on the anti cancer and apotosis inducing ability of NS seed extract in MCF-7 human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance and culture procedures were exactly similar to that of reported in our earlier study (Alshatwi et al, 2013). Briefly, The cell line was maintained and propagated in 90% Dulbecco's Modified Eagle's Medium (HyClone, Thermo Scientific, MA, USA) containing 10% fetal bovine serum (HyClone, Thermo Scientific) and 1% penicillin/streptomycin (HyClone, Thermo Scientific).…”
Section: Maintenance Of Mcf-7 Cellsmentioning
confidence: 99%
“…Crude extracts of fenugreek decreased the cell viability toward both drug-sensitive and drug-resistant cancer cell lines (Saeed et al, 2015). Methanol extracts from the whole plant induced cytotoxicity in MCF-7 breast cancer cells (IC 50 = 65 μg/mL; Alshatwi et al, 2013). In the same cell model, a chloroform extract also induced cytotoxicity (IC 50 = 41.6 μg/mL; Khoja et al, 2011).…”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…In the last several years, traditional methods used to fight cancer cells have been largely based on the use of plant natural products. Recent studies have reported that natural products have positive effects against cancer cells compared with chemotherapy (Kim et al, 2012;Wang et al, 2012;Alshatwi et al, 2013;Jung et al, 2014). Therefore, the present study was aimed to investigate the in vitro cytotoxic activity of two isolates of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%